Teori Konvergensi Perspektif Al-Qur’an Dan Hadits Tarbawi - Syahdan Muhammad Fauzi; Rahendra Maya (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
This article examines the theory of convergence from the perspective of the Qur’an and Prophetic traditions (hadith) on education (tarbawi). The study aims to identify Qur’anic verses and hadith that discuss the interaction between innate potential (nature) and environmental factors (nurture), analyze the convergence concept within the Islamic framework, and explore its implementation in Islamic Religious Education. This research employs a qualitative approach with library research methods, utilizing primary sources (Qur’an and hadith) and secondary sources (books, journal articles). The results indicate that: (1) the normative foundation of the fiṭrah concept in the Qur’an is firmly established through QS. Ar-Rum [30]: 30, QS. Al-A’raf [7]: 172, and QS. Al-Hadid [57]: 25, while the hadith narrated by al-Bukhari and Muslim from Abu Hurairah RA affirms that every child is born in a state of fiṭrah, yet parents significantly influence its direction; (2) the convergence theory in Islam shares similarities with William Stern’s theory in recognizing both innate and environmental factors, but fundamentally differs in its theocentric paradigm oriented toward ma’rifatullah, taqwa, and the realization of insān kāmil; (3) its implementation in Islamic Religious Education includes developing adaptive curricula based on fiṭrah, strengthening the synergy of three educational centers, the multidimensional role of PAI teachers, holistic assessment systems, character education based on fiṭrah, and convergence approaches in learning strategies.